2019
DOI: 10.26453/otjhs.454446
|View full text |Cite
|
Sign up to set email alerts
|

Hemşirelik Öğrencilerinin Bilimsel Araştırma Yapmaya Yönelik Kaygı ve Tutumlarının Belirlenmesi

Abstract: Bu çalışma, hemşirelik öğrencilerinin bilimsel araştırma yapmaya yönelik kaygı ve tutumlarının belirlenmesi amacıyla yapıldı. Tanımlayıcı ve kesitsel tipte olan çalışmanın evrenini, Türkiye'nin kuzey batısında yer alan bir üniversitenin hemşirelik bölümünde 2016-2017 eğitim öğretim yılında öğrenim gören öğrenciler oluşturdu. Örneklem seçiminde; evreni bilinen örneklem hesaplama formülü (%95 güven aralığı, %5 hata payı, %50 görülme sıklığı) kullanılmıştır. Hesaplama sonucuna göre örnekleme 162 öğrenci dahil edi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 12 publications
2
11
1
10
Order By: Relevance
“…In the present study, we observed that fourth-year nursing students had a more positive attitude toward scientific research and higher levels of academic self-efficacy compared to students in the other classes. Kes and Sahin (2019) and Unver et al (2017) also found that fourth-year nursing students had a more positive attitude toward scientific research than more junior students [8,22]. Furthermore, studies by Karadag et al (2011) and Zengin (2007) showed that academic self-efficacy level increases as students progress through their studies [4,23].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present study, we observed that fourth-year nursing students had a more positive attitude toward scientific research and higher levels of academic self-efficacy compared to students in the other classes. Kes and Sahin (2019) and Unver et al (2017) also found that fourth-year nursing students had a more positive attitude toward scientific research than more junior students [8,22]. Furthermore, studies by Karadag et al (2011) and Zengin (2007) showed that academic self-efficacy level increases as students progress through their studies [4,23].…”
Section: Resultsmentioning
confidence: 99%
“…A questionnaire including these scales was given to the students by the researchers. The student information form included some sociodemographic characteristics and was prepared by the researchers based on a literature review [1,2,6,8,18]. The ATSRS, developed in the Turkish language by Korkmaz et al (2011), is a 5-point Likerttype scale comprising 4 subdimensions [15].…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 3 more Smart Citations